The Effect of Consumer Trust and Perceived Risk on e-Wallet Adoption: Consideration for Technology Startup Entrepreneurs: Consideration for Technology Startup Entrepreneurs - Krisnawati, Melisa; Wienadi, Jessica; Wiradinata, Trianggoro (Universitas Ciputra Surabaya, 2021)
The use of electronic wallet (e-Wallet) has been increasingly popular due to the growth of electronic commerce because e-Wallet offers practicality and secure way of paying. However, data shows that payment by bank transfers are still the most popular payment method compared to e-Wallet. This study aims to analyze the effect of perceived usefulness, ease of use, consumer trust, and perceived risk towards the adoption of various kinds of e-wallet in Indonesia. The grounding theory of this study is using the Technology Acceptance Model (TAM) which is currently still very relevant in measuring antecedents toward technology adoption. This study collects data from 128 respondents using a self-administered questionnaire using purposive (judgmental) sampling. Among data collected there were 3 responds detected as outliers, hence removed. Multiple Regression Analysis was then performed using python programming language to determine significant factors. The finding of this study shows all antecedents are significantly affecting Intention to Adopt e-Wallet payment with Perceived Usefulness as the dominant factor. The finding is expected to inspire e-Wallet developers, integrators, and digital entrepreneurs to pay more attention towards the Perceived Usefulness factor.